An Overview of the Innate and Adaptive Immune System in Inflammatory Bowel Disease. Issue 1 (January 2017) - Choy, Matthew C.; Visvanathan, Kumar; De Cruz, Peter
Abstract : Abstract: Inflammatory bowel diseases (IBDs) are thought to develop as a result of complex interactions between host genetics, the immune system and the environment including the gut microbiome. Although an improved knowledge of the immunopathogenesis of IBDs has led to great advances in therapy such as the highly effective anti-tumor necrosis factor class of medications, a significant proportion of patients with Crohn's disease and ulcerative colitis do not respond to anti-tumor necrosis factor antibodies. Further understanding of the different immune pathways involved in the genesis of chronic intestinal inflammation is required to help find effective treatments for IBDs. In this review, the role of the mucosal innate and adaptive immune system in IBD is summarized, highlighting new areas of discovery which may hold the key to identifying novel predictive or prognostic biomarkers and new avenues of therapeutic discovery. Abstract : Article first published online 21 October 2016.